Stability analysis in safflower (Carthamus tinctorious L.): STABILITY ANALYSIS IN SAFFLOWER - INDU SWARUP; JAGDISH SINGH (Journal of Oilseeds Research, 2014)
The experiments were carried out at College of Agriculture, Indore in rabi season for consecutive three years viz., 2007-08, 2008-09 and 2009-10 with 28 genotypes of safflower. The observations were recorded on days to 50% flowering, days to maturity, plant height, branches/plant, capitula/plant, seeds/capitulum, hull content, 100-seed weight, seed yield/plant and harvest index. Analysis of variance revealed highly significant differences among genotypes for all the characters during all the three years. Non-significance of chi-square value suggested that the error variances were homogenous for all the traits under study. Pooled analysis indicated that the genotypes and environments differed among themselves and the genotypes showed differential performance over varying environments i.e., years/locations. The stability analysis as per the Eberhart and Russell model suggested the existence variability in the experimental materials and all the three environments differed significantly among themselves. Genotype x Environment (linear) was significant for days to maturity, number of capitula/plant and harvest index suggesting that the predictable portion of G x E interaction was more pronounced for the expression of these characters. The pooled deviation was significant for number of branches/plant, plant height, number of seeds/capitulum, hull content, 100-seed weight, days to maturity, number of capitula/plant, seed yield/plant and harvest index indicating the predominance of unpredictable portion of G x E interaction for the expression of these characters. Stable performance was exhibited by genotypes JSI-124 and JSI-135 for seed yield/plant and JSI 134 for earliness in maturity.